Study on factors affecting mortality in nonagenarian patients in orthopaedic surgery - Edipoglu, Ipek Saadet; Chousein, Chasan Memet; Balci, Halil Ibrahim; Buget, Mehmet Ilke (International Journal of Research in Medical Sciences, 2019)
Background: With medicine advancing, population is aging in the world. We encounter elderly patients in operating rooms more often. In this study, the aim was to investigate mortality and morbidity rates of patients 90 years of age or older within 1 year from the date of operation due to fractures. Methods: The study was performed retrospectively in the 3rd stage health institution. All patients that had fracture operation in the operating rooms of the orthopaedics department between 2011 and 2017 and that were 90 years or older on the day of operation were included in the study. Patients who were operated twice were excluded from the study. Results: Around 83 patients of which were included in the study. The mean age of the patients was 92.89±2.84. In-hospital mortality rate was 8.4%. The mortality rate within 3 months from the operation was 18.1%, 25.3% within 1 year, and 61.4% within 5 years or above. Author found that the mean survival period for the total of the surviving patients was 23.87±18.96 months. Author found that there was a meaningful causation between morbidity developing post-operation and in-hospital mortality, 3-month mortality, and 1-year mortality (p<0.05). Conclusions: Author think that it was important to recognize the fact that despite being more vulnerable, patients 90 years of age or older have a significant life expectancy post-hospital discharge. Author think that post-operation acute morbidity affects mortality rates and it was important to avoid factors that may cause acute morbidity in patients 90 years of age and older.